Femoroacetabular impingement: a common cause of hip pain - Menge, T. J.; Truex, N. W. (The Physician and Sportsmedicine, 2018)
Femoroacetabular impingement (FAI) is a common cause of hip pain that can affect a wide range of patients. It is due to altered bony morphology of the proximal femur and acetabulum, resulting in decreased function and progression to early osteoarthritis. Until the early 2000s, little was known or understood about the significance of FAI as a clinical entity. The field of hip preservation has grown exponentially since that time, and has led to many advances in caring for those with symptomatic impingement. This review details the early diagnosis and proper management of femoroacetabular impingement for the sports medicine practitioner.